Records guardianship: security and protection in the workplace - Louko , Coralee (Archives & Manuscripts, 2012)
Ensuring the proper protection of records presents numerous challenges. The archival community has adequately addressed how to recognise, and deal with, threats to the conservation and preservation care of records, but security risks in the workplace are often not given appropriate attention. The identification of potential sources of risk, at all stages of a record’s existence, and the discovery of solutions to prevent or mitigate these risks is crucial to guaranteeing the ongoing care and complete protection of records of all types.